EFFICIENCY OF FERMENTED SEAWEED EXTRACT AS FOLIAR FERTILIZER AT VARYING FREQUENCY AND CONCENTRATION IN PEANUT (Arachis hypogaea L.) PRODUCTION - Juliet Bangi; Fatima Sheirene M. Marajuli (SEAMEO BIOTROP, 2024)
Fermented seaweed extract (FSE) was used as fertilizer in peanut production at MSU Sulu –BARMM, Philippines. The experiment was set up in a 3 x 5 factorial in split-plot randomized complete block design (RCBD), with the main plot (A) as the frequency of the fertilizer applied - once a week, twice a week, and once a month while, the sub-plot (B) as the concentration at 5, 10, 15, and 20%. The application of fermented seaweed extract significantly influenced the growth parameters and yield responses in peanut production. The treatment combinations of once- and twice-a-week application of 5-10% fermented seaweed extract provided the best results in peanut growth and yield. FSE applied twice a week at 5% concentration gave the highest yield of 2.49 tons per hectare. Peanut applied with FSE once a week at a 5% concentration gave the lowest cost of expenses and the highest return on investment of 179%.